Amorphophallus muelleri activates ferulic acid and phenylpropane biosynthesis pathways to defend against Fusarium solani infection - Gao, Penghua; Qi, Ying; Li, Lifang; Yang, Shaowu; Liu, Jiani; Wei, Huanyu; Huang, Feiyan; Yu, Lei (Frontiers in Plant Science, 2023)
Amorphophallus sp. is an economically important crop for rural revitalization in southwest China. However, Fusarium solani often infects Amorphophallus sp. corms during storage, damaging the corm quality and affecting leaf elongation and flowering in the subsequent crop. In this study, the mechanism of resistance to F. solani was investigated in the leaf bud and flower bud corms of Amorphophallus muelleri through transcriptome and metabolome analyses. A total of 42.52 Gb clean reads and 1,525 metabolites were detected in a total of 12 samples including 3 samples each of disease-free leaf bud corms (LC), leaf bud corms inoculated with F. solani for three days (LD), disease-free flower bud corms (FC), and flower bud corms inoculated with F. solani for three days (FD). Transcriptome, metabolome, and conjoint analyses showed that 'MAPK signal transduction', 'plant-pathogen interaction', 'plant hormone signal transduction', and other secondary metabolite biosynthesis pathways, including 'phenylpropane biosynthesis', 'arachidonic acid metabolism', 'stilbene, diarylheptane and gingerolin biosynthesis', and 'isoquinoline alkaloids biosynthesis', among others, were involved in the defense response of A. muelleri to F. solani. Ultimately, the expression of six genes of interest (AmCDPK20, AmRBOH, AmWRKY33, Am4CL, Am POD and AmCYP73A1) was validated by real-time fluorescence quantitative polymerase chain reaction, and the results indicated that these genes were involved in the response of A. muelleri to F. solani. Ferulic acid inhibited the growth of F. solani, reducing the harm caused by F. solani to A. muelleri corms to a certain extent. Overall, this study lays a strong foundation for further investigation of the interaction between A. muelleri and F. solani, and provides a list of genes for the future breeding of F. solani-resistant A. muelleri cultivars.